2021
DOI: 10.3390/ijerph18189808
|View full text |Cite
|
Sign up to set email alerts
|

A 4 mm-Long Implant Rehabilitation in the Posterior Maxilla with Dynamic Navigation Technology: A Case Report after a Three-Years Post-Loading Follow-Up

Abstract: The use of short (<8 mm long) and ultra-short (<6 mm long) implants allows the prosthetic rehabilitation of the posterior ridges of the jaws avoiding reconstructive procedures. Nevertheless, this approach requires vast experience to ensure the primary stability of the fixture in a correct position. Computer-aided implantology (CAI) achieves better results than the free-hand one in terms of placement accuracy, reducing the surgical risks and the operative timings. Dynamic navigation (DN) allows the surgeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Dental elements are more and more used as anatomical fiducial markers, called dental surface calibration. Surface calibration (dental and bone), also called "trace registration" [32] are technologies about to save operative time, by avoiding to use thermoplastic brackets and to perform a 2 nd imaging for a point calibration using radiological markers [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dental elements are more and more used as anatomical fiducial markers, called dental surface calibration. Surface calibration (dental and bone), also called "trace registration" [32] are technologies about to save operative time, by avoiding to use thermoplastic brackets and to perform a 2 nd imaging for a point calibration using radiological markers [8].…”
Section: Discussionmentioning
confidence: 99%
“…This review showed that the use of navigation in implantology is prominent, representing 19 articles (55%). A total of 631 implants were placed; short implant [8], pterygoid implant [9] and zygomatic implants [10][11][12][13][14]. The indications were varied; rehabilitation of the edentulous jaw using immediate implant loading with fixed prothesis, extraction-implantation, single implant in aesthetic zone [10,11,[15][16][17], single implant with immediate loading in aesthetic zone [18] or the placement of standard minimally invasive implants (flapless) [19].…”
Section: Implantologymentioning
confidence: 99%